2017
DOI: 10.1038/s41467-017-00988-5
|View full text |Cite
|
Sign up to set email alerts
|

NatD promotes lung cancer progression by preventing histone H4 serine phosphorylation to activate Slug expression

Abstract: N-α-acetyltransferase D (NatD) mediates N-α-terminal acetylation (Nt-acetylation) of histone H4 known to be involved in cell growth. Here we report that NatD promotes the migratory and invasive capabilities of lung cancer cells in vitro and in vivo. Depletion of NatD suppresses the epithelial-to-mesenchymal transition (EMT) of lung cancer cells by directly repressing the expression of transcription factor Slug, a key regulator of EMT. We found that Nt-acetylation of histone H4 antagonizes histone H4 serine 1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 49 publications
4
97
0
Order By: Relevance
“…However, the presence of H4S1 ph may be influenced by the acetylation state of the alpha amino group of H4S1, since recent evidence supports that CK2α prefers to bind to an H4 peptide without N-terminal acetylation versus an H4 peptide that is N-terminally acetylated. [85] While we have not observed a preference for the predominant PRMTs (PRMT1 and PRMT5) to methylate H4 with or without N-terminal acetylation, the presence of N-terminal acetylation may serve to prevent phosphorylation of H4S1 and thereby provide a better substrate for PRMTs to methylate H4. In contrast, the lack of N-terminal H4 acetylation by NatD can promote phosphorylation of H4S1 and may be overall inhibitory to PRMT catalyzed methylation of H4R3.…”
Section: Interplay Of Arginine Methylation With Other Ptm Marks On Himentioning
confidence: 58%
“…However, the presence of H4S1 ph may be influenced by the acetylation state of the alpha amino group of H4S1, since recent evidence supports that CK2α prefers to bind to an H4 peptide without N-terminal acetylation versus an H4 peptide that is N-terminally acetylated. [85] While we have not observed a preference for the predominant PRMTs (PRMT1 and PRMT5) to methylate H4 with or without N-terminal acetylation, the presence of N-terminal acetylation may serve to prevent phosphorylation of H4S1 and thereby provide a better substrate for PRMTs to methylate H4. In contrast, the lack of N-terminal H4 acetylation by NatD can promote phosphorylation of H4S1 and may be overall inhibitory to PRMT catalyzed methylation of H4R3.…”
Section: Interplay Of Arginine Methylation With Other Ptm Marks On Himentioning
confidence: 58%
“…Other types of interplay include NatD-mediated histone H4 Nt acetylation, which has been found to block H4Arg3 methylation in one case and H4Ser1 phosphorylation in another, affecting transcription from such promoters (Ju et al, 2017;Schiza et al, 2013). A recent study found an inverse relationship between protein Nt ubiquitination and Nt acetylation (Akimov et al, 2018).…”
Section: Regulation Of Nt Acetylationmentioning
confidence: 99%
“…NatD is essential for colon cancer cell survival (Pavlou and Kirmizis, 2016). In primary human lung cancer, NatD has been found to be upregulated and correlated with decreased survival rates (Ju et al, 2017). Cancer migration is mediated via Slug and repression of the epithelial-to-mesenchymal transition.…”
Section: Molecular Cellmentioning
confidence: 99%
“…Chromatin remodeling and histone modifications, both methylation and acetylation, have been recognized as major mechanisms controlling gene transcription (30,31). A recent study showed that NatD acetylates histone H4 serine 1 (S1), which blocks CK2a-mediated S1 phosphorylation, and allows H4R3 methylation and H4K5 acetylation to activate SLUG gene expression, which promotes EMT to increases cancer cell invasion and metastasis (32). Our findings deciphered the molecular mechanism of SND1 used as a novel coactivator for SLUG.…”
Section: Discussionmentioning
confidence: 60%